The self-activation and LPS binding activity of executioner caspase-1 in oyster Crassostrea gigas. (December 2017) - Lu, Guangxia; Yu, Zichao; Lu, Mengmeng; Liu, Dongyang; Wang, Feifei; Wu, Yichen; Liu, Yu; Liu, Chao; Wang, Lingling; Song, Linsheng
Abstract: Executioner caspases play important roles in apoptotic pathway and immune defense, which is considered to coordinate the execution phase of apoptosis by cleaving multiple structural and repair proteins. However, the knowledge about the activation mechanism and function of executioner caspases in mollusks, especially marine bivalves is limited. In the present study, the full-length cDNA sequence of caspase-1 was cloned from oyster Crassostrea gigas, which encoded a predicted protein containing a small subunit (p10) and large subunit (p20) with a conserved caspase active site QACRG similar to that of human executioner caspase-3/7. SDS-polyacrylamide gel electrophoresis and western blot results demonstrated that the Cg Caspase-1 zymogen could be cleaved into p20p10, p20 and p10 in prokaryotic expression systems, and the C-terminus of Cg Caspase-1 was also cleaved into p20 and p10. Both of the recombinant Cg Caspase-1 (r Cg Caspase-1) and the C-terminus of Cg Caspase-1 (r Cg Caspase-1-C) exhibited similar caspase activity towards proteolytic substrate Ac-DMQD-pNA and Ac-DEVD-pNA. However, the recombinant N-terminus of Cg Caspase-1 (r Cg Caspase-1-N) did not display any caspase activity. Moreover, the inhibitor of both caspase-3/7 and pan-caspase could significantly inhibit the proteolytic activity of r Cg Caspase-1. The strong binding activities towards lipopolysaccharide (LPS) of both r Cg Caspase-1 and r Cg Caspase-1-C were revealed by ELISA techniques and western blotting. A high level of Cg Caspase-1 mRNA transcripts was detected in the gills and hemocytes by quantitative real-time PCR, and the Cg Caspase-1 protein was mainly located in the cytoplasm of oyster hemocytes by immunofluorescence assay. These results collectively suggested that Cg Caspase-1 was a homolog of executioner caspase-3/7, which could be self-activated through proteolytic cleavage in prokaryotic expression systems, and performed caspase and LPS binding activities in the innate immune response of oyster. Highlights: Cg Caspase-1 is a homolog of executioner caspase-3/7 in oyster. Cg Caspase-1 was cleaved into p20p10, p20 and p10 in prokaryotic expression system. r Cg Caspase-1 and r Cg Caspase-1-C both exhibited activities of caspase-3/7 and LPS binding in a dose-dependent manner. Cg Caspase-1 was higher expressed in the gills, and the protein was mainly localized in the cytoplasm of hemocytes.